Forum: Dictionary of Terms in Fine Arts and Architecture. Volume III, L–O - Milašinović Marić, Dijana (Arhitektura i urbanizam, 2024)
At the SANU Library forum organized on February 6, 2024, the third volume of the Dictionary of Fine Arts and Architecture was spoken by: academician Mrđan Bajić, academician Miodrag Marković, Ph.D. Ljiljana Stošić and Ph.D. Dijana Milašinović Marić on behalf of Academician Milan Lojanica.The latest third volume of the Dictionary of terms of fine arts and architecture, the so-called Blue book, was published at the end of last year to the great joy, pride and admiration of all members of the editorial staff as well as the publisher. Exactly according to the plan, the projection of the dynamics of publication, three years after the second volume, the third one was published as a result of concentrated energy, knowledge, enthusiasm and summarizing the experience of the entire editorial team, which, decades after the publication of the first one, is already steadily reaching for the next one, the fourth one.
Keywords: Dictionary; The terms; Architecture; Fine art